Literatura no Ensino Médio à luz da pesquisa sócio-histórico-cultural: rompendo cápsulas - Rolando, Rodolfo Meissner (2018)
The main purpose of this dissertation is to investigate if and how the Social-Cultural-Historical Activity Theory can contribute to encapsulation breaking of the teaching of literature for high school students. This study also aims to promote the education of students who are able to think critically and to relate the curriculum to their actions in society. According to Cereja (2005), Cosson (2006 , 2014), Paulino e Cosson (2009) and Zilberman and Rösing (2009), the teaching of literature in secondary schools faces a serious crisis. As reported by these researchers, in general, teachers of Brazilian literature use traditional teaching methods, separating school learning from political and socio-historical questions. This problem seems to have been worse at the technical school where this research was conducted. This school focuses on providing technical training for students who will enter the labor market. In doing so, there is not sufficient time for overcoming the literature curriculum, in consonance with Engeström’s (1991) concept of encapsulation in school learning. That way this research intended to plan the teaching of Brazilian literature to arouse the students’ interest and to foster the development of citizenship. This study tries to answer the following questions: 1.a) How are some concepts in literature formulated and discussed in the classroom? 1.b) How it is the relationship between these concepts and the sociocultural reality which emerges from the participants’ discussions?; 2. How are the relationships in the classroom (re)established and how are the teacher’s and the students’ roles (re)defined throughout the research? On a methodological level, this investigation uses the critical collaborative research. This methodology was chosen because it suggests a school-based intervention and an educational change. It focuses largely on developing collaborative relationships amongst the participants. They may take up a more critical stance as well. The literature review includes the Vygotskian perspective on the human psyche, as it was proposed in the Social-Cultural-Historical Activity Theory by Engeström (2011, 2016), Stetsenko (2011), Liberali (2011) and Magalhães (2012). In addition, it includes the studies on critical collaboration by Magalhães (2010, 2011, 2014, 2016) and on the dialogic perspective on language by the Bakhtinian Circle. The data was generated in the literature classes for freshmen of high school during the 2017 first semester. All these classes were videotaped. The findings indicate that the encapsulation of the teaching of literature for high school students was broken. Besides, the teacher’s and the students’ roles were redefined. At last the research enabled the teacher-researcher to reflect critically on the capsules which were restraining his pedagogical practices